Further development of satellite telecommunications radio signals noise immunity increasing method - Kozelkov, Serhii; Shulha, Oleksandr; Shefer, Oleksandr; Neliuba, Dmytro (International Journal of Engineering and Technology, 2018)
The problem of radio communication loss during spacecraft passage at hyperspeed through dense layers of atmosphere at heights of 60-120 km as result of plasma ionization shock wave formation is analyzed. As a result, this part of spacecraft trajectory is the most problematic from navigation and control point of view. A part of this unsolved problem is identified and an innovative method for solving it is proposed â€“ a method of resonant radio signal regeneration developed, which based on interaction of outer ionized layer elementary particles with artificially generated high intensity negative radiation. Technical means for artificial low-temperature plasma energy-efficient formation have been developed. A design for equipotential low-temperature plasma of high intensity, which based on near-cathode region glow discharge and depends on electrodes geometric parameters and gaseous medium physical parameters proposed. This method, in comparison with existing spacecraft radio communication methods, does not introduce changes into spacecraft external design and does not affect flight aerodynamics. High-temperature plasma shell with artificial intense negative radiation interaction simulation confirms the formation of resonant regenerative transport layer that facilitates radio signal passage through plasma ionization shock wave around spacecraft.Â Â